Kazakhstan’s Policy Towards Cooperation in Higher Education with China, the US and Turkey - Anastasia Pogorelskaya; Evgeny Troitskiy; Gulmira Mussina (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. Since 2022 Kazakhstan has noticeably intensified cooperation with China, Turkey, and the US in higher education, providing their universities with favorable conditions for opening branches and implementing scholarship programs to recruit Kazakhstani applicants. The research novelty is the assessment of current Kazakhstani educational cooperation as a tool for balancing Russian influence in Kazakhstan and Central Asia in general. The choice of partner countries is justified by a noticeable recent expansion of their presence in Kazakhstan’s higher education. Methods and materials. The research is based on the analysis of Kazakhstani official documents; speeches and statements by the officials of Kazakhstan, China, Turkey, and the US; the activities of foreign universities in Kazakhstan, reflected primarily in the functioning of foreign branches and inter-university contacts; and statistical data characterizing the situation in Kazakhstan’s higher education system. The research theoretical basis is provided by the concept of soft balancing and higher education internationalization. Analysis. The authors established the rationales behind intensifying Kazakhstan’s cooperation in higher education with particular foreign partners, namely China, Turkey, and the US; determined the scale and formats of such educational cooperation; and indicated intermediate results of this policy. Results. A forecast for the development of higher education in Kazakhstan was developed and recommendations were formulated for Russia on educational cooperation with Kazakhstan. Authors’ contribution. E.F. Troitskiy provided the concept of the article, theoretical and literature review. A.M. Pogorelskaya analyzed the educational cooperation between Kazakhstan and its foreign partners. G.S. Mussina compiled a forecast for higher education development in Kazakhstan and elaborated the recommendations.